Theories of culture - Groh, Arnold (Abingdon, Oxon : Routledge, 2020)
This authoritative but concise guide describes the most significant cultural theories from the 19th to the 21st century and their originators, as well as the links between them and their mutual influences. This guide explores ideas around what culture is, when and why cultures change over time and whether there are any rules or principles behind culture-related phenomena and processes. For those seeking to answer questions on culture, familiarity with these topics is essential. From refugee movements caused by wars, to the ongoing demographical changes in regions of the world like sub-Saharan Africa or the Indian subcontinent, understanding the underlying mechanisms of culture-related processes has become an immediate and essential task. Covering everything from the processes of cultural change to counterculture and destabilisation, the book explains different ideas in a clear and objective fashion and includes approaches that have been unduly neglected but which have high explanatory value regarding culture and its phenomena. Providing readers with an up-to-date idea of what culture is, and how our understanding of it has been established over the past century, this text is the perfect companion for advanced undergraduates, postgraduates and researchers.
Introduction 1. Views from a Distance 2. Some Perspectives on Cultural Change 3. Structures of Culture 4. Culture as a Storage of Information 5. Finding Answers 6. The Individual and Cultural Context 7. Internal Perspectives 8. External Perspectives 9. Meta Perspectives 10. Disillusions Conclusion Appendix References Index of Persons Subject Index
Prof. Dr. Arnold Groh is head of the Structural Analysis of Cultural Systems research unit, which is in Special Consultative Status with the United Nations Economic and Social Council. He teaches as a private lecturer at the Technical University of Berlin, Germany. -- Back cover.
Includes bibliographical references (pages 306-325) and indexes.
Keywords: Culture; Culture -- History